Hell of a book : or the altogether factual, Wholly Bona Fide story of a big dreams, hard luck, American-Made Mad Kid - Mott, Jason (Dutton, 2021)
"From a New York Times bestselling author, an astounding work of fiction, both incredibly funny and heartfelt, asking readers to embrace the fantastical in order to get to the heart of racism, police violence, and the hidden costs exacted upon not only Black Americans, but America as a whole"--